Maturity z matematiky včera a dnes - Svobodová, Gabriela; Šišma, Pavel, 1964-; Masarykova univerzita. Ústav matematiky a statistiky (2012)
Bakalářská práce „Maturity z matematiky včera a dnes" obsahuje třicet řešených příkladů doplněných komentářem. Tyto úlohy byly předloženy studentům gymnázia ve školním roce 1935/1936. Komentář je zaměřen na posouzení obtížnosti zadané úlohy vzhledem k obsahu historických učebnic z třicátých let minulého století. Dále je zde posouzeno, zda by danou úlohu byli schopni vyřešit nynější gymnaziální studenti.
The Bachelor Thesis "The Mathematics Graduation in the Past and Now" consists of thirty solved problems that come along with commentaries. These examples were solved by high school students in the school year 1935/1936. The commentaries focus on the assessment of difficulty in relation to the content of historical textbooks. Furthermore, another assessment deals with the question whether current high school students are able to solve the same problems.
Vedoucí práce: Pavel Šišma
Bakalářská práce (Bc.)--Masarykova univerzita, Přírodovědecká fakulta, 2012
Keywords: 1935; 1936; dějiny matematiky -- Česko -- 20. století; matematika; maturitní zkoušky; high school equivalency examinations; history of mathematics -- Czechia; history of mathematics; mathematics; bakalářské práce; bachelor's theses